Measurements of W+W- production in decay topologies inspired by searches for electroweak supersymmetry - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (The European physical journal. C, Particles and fields, 2023)
This paper presents a measurement of fiducial and differential cross-sections for W+W- production in proton-proton collisions at √s = 13 TeV with the ATLAS experiment at the Large Hadron Collider using a dataset corresponding to an integrated luminosity of 139 fb-1. Events with exactly one electron, one muon and no hadronic jets are studied. The fiducial region in which the measurements are performed is inspired by searches for the electroweak production of supersymmetric charginos decaying to two-lepton final states. The selected events have moderate values of missing transverse momentum and the ‘stransverse mass’ variable mT2, which is widely used in searches for supersymmetry at the LHC. The ranges of these variables are chosen so that the acceptance is enhanced for direct W+W- production and suppressed for production via top quarks, which is treated as a background. The fiducial cross-section and particle-level differential cross-sections for six variables are measured and compared with two theoretical SM predictions from perturbative QCD calculations.